Ecology and food quality of fishes in coastal rivers of the far north of Ontario - Heerschap, Matthew J. (Laurentian University of Sudbury, 2017)
The Far North of Ontario is home to over 24 000 people in 31 communities, and many of these people rely heavily on wild fish as part of their diet. Six of these communities are situated on the lower reaches of large river systems near the coast of Hudson and James Bays. These large rivers, as well as numerous smaller rivers along the coast, are home to a variety of fish species, including some presumed anadromous (migrating between fresh and salt water) populations, that support important subsistence fisheries. However, little research has been carried out on fish resources of these river systems, and basic information is generally lacking. I examined fish populations from the lower reaches of 14 of these rivers in terms of growth, trophic ecology, life history, and their suitability for human consumption based on mercury and fatty acid content. Stable isotope and fatty acid compositions indicative of predation on marine food sources were most evident in the presumed anadromous species - Brook Trout, Lake Whitefish and Cisco. Compared to inland lakes of the same drainage basins, coastal river populations of Northern Pike and Walleye grew faster and occupied broader trophic niches, suggestive of an indirect marine influence on their diet. In contrast, Lake Whitefish tended to grow more slowly in coastal rivers than in inland lakes. Fish mercury concentrations in coastal rivers have not changed appreciably over the last ~ 30 years. Current fish mercury concentrations did not vary latitudinally among coastal rivers, but were significantly higher than in inland lakes for Walleye, Lake Whitefish and White Sucker. Fillet lipid and essential fatty acid (EPA+DHA) content decreased with increasing latitude in Northern Pike, but not in other species. Both mercury and essential fatty acid concentrations of fish muscle varied among rivers but there did not appear to be spatial concordance between them. Presumed anadromous species - Brook Trout, Lake Whitefish, Cisco – tended to have both the greatest concentrations of ...